2009
DOI: 10.1183/09031936.00158008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of formoterol and salmeterol on cytokine release from monocyte-derived macrophages

Abstract: Pulmonary macrophages are a target for inhaled therapies. Combinations of longacting b 2 -agonists (LABA) and glucocorticosteroids have been developed for asthma and chronic obstructive pulmonary disease (COPD). This study examined two LABA, salmeterol and formoterol, and the glucocorticosteroid, budesonide, on cytokine release from monocytederived macrophages (MDM) to determine whether anti-inflammatory effects observed in patients are due to inhibition of macrophages.MDM were incubated in the absence or pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 51 publications
4
38
1
Order By: Relevance
“…Salmeterol and indacaterol were reasonably effective inhibitors of cytokine generation from lung macrophages whereas formoterol was ineffective. These findings differ with those reported for MDM in which both formoterol and salmeterol were capable of reducing the extent of LPS-induced cytokine generation (Donnelly et al, 2010). Indeed, our own studies indicate that all the short-acting -agonists tested (isoprenaline, salbutamol and terbutaline) as well as the long-acting -agonist formoterol are considerably more effective inhibitors of cytokine generation in MDM than in lung macrophages (Fig.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Salmeterol and indacaterol were reasonably effective inhibitors of cytokine generation from lung macrophages whereas formoterol was ineffective. These findings differ with those reported for MDM in which both formoterol and salmeterol were capable of reducing the extent of LPS-induced cytokine generation (Donnelly et al, 2010). Indeed, our own studies indicate that all the short-acting -agonists tested (isoprenaline, salbutamol and terbutaline) as well as the long-acting -agonist formoterol are considerably more effective inhibitors of cytokine generation in MDM than in lung macrophages (Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…Attenuating excessive macrophage activation would be expected to be benefical in the treatment of respiratory diseases. Studies investigating the effects of -agonists on monocytes, monocyte-derived macrophages (MDM) and macrophagelike cell lines suggest that these drugs may modulate a number of macrophage functions including the prevention of pro-inflammatory cytokine generation (Yoshimura et al, 1997;Izeboud et al, 1999;Donnelly et al, 2010;Shirato et al, 2013). By contrast, other studies show limited effects of -agonists in these systems (Linden, 1992;Zetturlund et al, 1998;Ezeamuzie and Shihab, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure, affinity, efficacy, kinetics, and ability to elevate intracellular cAMP vary for salmeterol and formoterol (57,65), which could explain the differences observed. We also assessed the effect of increasing intracellular cAMP by inhibiting PDEs.…”
Section: Discussionmentioning
confidence: 91%
“…The combination of a bronchodilator with an anti-inflammatory agent as a treatment of COPD has been extensively discussed and is reviewed in Phillips and Salmon (2012). The ability of b 2 -adrenoceptor agonists to also have direct anti-inflammatory activity has been previously described, including inhibition of histamine, arachidonic acid metabolites, and TNFa release from mast cells (Undem et al, 1988;Bissonnette and Befus, 1997;Chong et al, 1998) and on cytokine release from monocytes (Seldon et al, 2005;Donnelly et al, 2010). Previous studies from this laboratory and others have shown the effects of roflumilast combined with salmeterol, formoterol, or dexamethasone on lipopolysaccharide (LPS)-induced peripheral blood mononuclear cells (PBMC) cytokine production, showing additive effects for PDE4 inhibition with either a LABA or glucocorticosteroid (Seldon et al, 2005;Tannheimer et al, 2012a), suggesting an additional anti-inflammatory effect in combination or possible triple combination.…”
Section: Introductionmentioning
confidence: 99%